Structure-Sensitive Properties of Cu-Based Binary Subsystems of High-Entropy Bi–Cu–Ga–Sn–Pb Alloy - Dufanets, M.; Sklyarchuk, V.; Plevachuk, Yu. (Ukrainian Journal of Physics, 2020)
The temperature dependences of the viscosity, electrical conductivity, and thermal emf of the binary melts Cu50Bi50, Cu50Ga50, Cu50Pb50, and Cu50Sn50 with equiatomic concentrations, which are components of the high-entropy Bi–Cu–Ga–Sn–Pb alloy, have been studied. Based on the obtained results, the activation energy of the viscous flow and the configurational entropy of mixing are calculated. The obtained negative values of the mixing entropy testify to a structural ordering in the system.